The Role of the Naqshbandiyah Order as an Islamic Educational Institution in Riau - Supianto, Supianto; Apriansah, Feri; Roza, Ellya (Universitas Pahlawan Tuanku Tambusai, 2026)
Background: Tarekat Naqsabandiyah serves as a vital non-formal Islamic educational institution in Riau, Indonesia, integrating spiritual practices like suluk and dhikr khafi with moral and social formation amid modern challenges. Purpose: This study examines the role of Tarekat Naqsabandiyah as an Islamic educational institution in Riau. Method: Qualitative library research employs a historical-sociological approach. Population and Sample: Population comprises literature on Tarekat Naqsabandiyah in Riau (2000–2025); purposive sampling yields 50 key documents. Instruments and Data Analysis: Documents from Google Scholar undergo descriptive-analytic analysis with thematic coding and triangulation. Results: Findings reveal suluk, halaqah, and khalifah systems foster spiritual-moral character, with adaptations like digital literacy and social services ensuring relevance. Conclusion: Tarekat Naqsabandiyah sustains transformative Islamic education, recommending empirical field studies for future research.